2015
DOI: 10.1002/mc.22334
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of RAD52 as a lung cancer susceptibility gene in the 12p13.33 locus

Abstract: Recent genome-wide association studies have identified variations in the recombination repair gene, RAD52, that are associated with increased lung cancer risk, and particularly with the development of lung squamous cell carcinomas (LUSC). LUSC development is strongly associated with smoking. DNA repair is increased in the lung tissues of smokers, presumably because of ongoing DNA damage from exposure to tobacco smoke. A key player in the DNA damage response, RAD52 plays a role in DNA strand exchange and anneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 25 publications
0
30
0
1
Order By: Relevance
“…Moreover, although it was not evident in our data set (Fig. 6G) the overexpression of RAD52 has been shown to be associated with lung squamous cell carcinomas genesis and progression [85]. Lastly, the relative overexpression of RAD52 was also shown to lead to earlier mortality in a mouse model genetically engineered to be predisposed to colorectal carcinomas [43].…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, although it was not evident in our data set (Fig. 6G) the overexpression of RAD52 has been shown to be associated with lung squamous cell carcinomas genesis and progression [85]. Lastly, the relative overexpression of RAD52 was also shown to lead to earlier mortality in a mouse model genetically engineered to be predisposed to colorectal carcinomas [43].…”
Section: Discussionmentioning
confidence: 75%
“…12p13.33 amplification appeared in all the lymph nodes and in the primary tumor of this patient. A recent study reported that the recombination repair gene RAD52, within the 12p13.33 region, is associated with the risk of lung squamous cell carcinoma development (31). The expression level of genes belonging to the targetable PI3K/RTK/RAS oncogenic pathway were observed to be above background expression levels of the TCGA squamous cell carcinoma cohort (n ¼ 495; Supplementary Fig.…”
Section: Correlation Of Treatment Responses With Clonal Evolution Patmentioning
confidence: 88%
“…A role for Rad52 in BIR can explain why its depletion in cells with DRS leads to increased DNA damage (Wray et al., 2008, Murfuni et al., 2013, Galanos et al., 2016; Figures 3A and 3B), why the RAD52 gene is amplified in human cancers, and why its inactivation curtails cancer development (Treuner et al., 2004, Cramer-Morales et al., 2013, Lieberman et al., 2016; Figure 4). BIR also mediates DNA repair synthesis in mitosis (Minocherhomji et al., 2015), and it is noteworthy that Rad52 is essential also in this context (Bhowmick et al., 2016).…”
Section: Discussionmentioning
confidence: 99%